1996
DOI: 10.1099/0022-1317-77-4-753
|View full text |Cite
|
Sign up to set email alerts
|

Rapid selection for an N-linked oligosaccharide by monoclonal antibodies directed against the V3 loop of human immunodeficiency virus type 1

Abstract: The V3 loop of the human immunodeficiency virus (HIV) surface protein, gpl20, constitutes a principal neutralizing determinant. HIV strains lacking a naturally conserved N-linked oligosaccharide (at position 306) within the V3 loop are highly sensitive to neutralization. We subjected molecular clones of HIVLA ~ lacking this 3°6N-glycan to in vitro immune selection with MAbs directed against the V3 loop. In all, ten clones were characterized, and all proved resistant to V3-directed neutralization. Sequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 28 publications
3
34
1
Order By: Relevance
“…A second line of evidence comes from studies with both human and animal lentiviruses, where variation in the envelope glycoproteins frequently results in the deletion, addition, or relocation of potential N-linked glycosylation sites, suggesting a role for immune selection in the evolution of viral variants. These variation studies are further supported by the observation that the binding and neutralizing properties of some HIV-1 monoclonal antibodies (MAbs) are affected by changes in N-linked glycosylation (2,4,5,16,45). Recent studies also suggest that glycosylation in the V1, V2, and V3 regions may play critical roles in determining HIV-1 gp120 interactions with receptors (22,37,38) and in preventing access of neutralizing antibodies to the receptor binding domains (31).…”
mentioning
confidence: 68%
“…A second line of evidence comes from studies with both human and animal lentiviruses, where variation in the envelope glycoproteins frequently results in the deletion, addition, or relocation of potential N-linked glycosylation sites, suggesting a role for immune selection in the evolution of viral variants. These variation studies are further supported by the observation that the binding and neutralizing properties of some HIV-1 monoclonal antibodies (MAbs) are affected by changes in N-linked glycosylation (2,4,5,16,45). Recent studies also suggest that glycosylation in the V1, V2, and V3 regions may play critical roles in determining HIV-1 gp120 interactions with receptors (22,37,38) and in preventing access of neutralizing antibodies to the receptor binding domains (31).…”
mentioning
confidence: 68%
“…It has been reported previously that glycans shield antibody epitopes (29,32,36,45). Very recently, Wei et al (45) showed that NAbs directed towards HIV gp160 exert sufficient viral inhibitory activity to force the virus to replace the neutralization-sensitive virus by successive populations of resistant virus.…”
Section: Vol 78 2004 Hiv Resistance To Mannose-specific Plant Lectimentioning
confidence: 99%
“…However, no reduction of CCR5 usage was observed when the same residue was mutated on SF13 and SF162 (M-tropic) (34) or ConB (M-tropic) (51). Additionally, the corresponding mutation had no effect on infectivity of other T-tropic stains (LAI, BRU, and HXB2 [2,27,43]). These apparent discrepancies are likely due to specific differences in amino acid sequences in the V3 loop for different isolates, which together with carbohydrate residues create a V3 loop …”
Section: Discussionmentioning
confidence: 96%